The present as history : critical perspectives on contemporary global power - Shaikh, Nermeen (Columbia University Press, 2007)
The Present as History is a rare opportunity to hear world-renowned scholars speak on the new imperialism, feminism and human rights, secularism and Islam, post-colonialism, and the global economy. They treat the United States as an object to be historically and politically interrogated rather than as the norm from which all else is to be evaluated and assess the Third World through its history of colonialism and neocolonialism rather than focusing on issues of culture and morality. Amartya Sen discusses the shortcomings of the development agenda as it was conceived at th.